Development of triphasic calcium phosphate–carbon nanotubes (HA/TCP-CNT) composite: a preliminary study - Gunawan, Gunawan; Sopyan, Iis; Nurfaezah, Siti; Ammar, Mohd (Trans Tech Publications, Switzerland, 2013)
Triphasic calcium phosphate, composed of a more stable phase hydroxyapatite (HA) and highly soluble tricalcium phosphates (α- and β-TCP) has been synthesized through hydrothermal method. In the present work, an in-situ method to disperse 1wt% multiwall carbon nanotubes (MWCNTs) within HA/TCP powder has been used in order to develop HA/TCP-CNTs composite. XRD results confirmed the formation of HA, α-TCP and β-TCP in both as-prepared powder and composite samples. The graphite peaks appeared in the composite samples as well. FTIR analysis of sintered compacted powder showed the formation of weak bands of PO43- as the temperature was increased. The sintered compacts were mechanically tested by Vickers microhardness indentation method. HA/TCP-CNTs composite was found to have a significant of Vickers Hardness of 1.98 GPa after 1100oC sintering. The morphology analysis showed that in-situ deposition technique provides homogeneous dispersion of CNTs in the calcium phosphate matrix.